Off-design thermodynamic performances of a combined solar tower and parabolic trough aided coal-fired power plant - Liu, Hongtao; Zhai, Rongrong; Patchigolla, Kumar; Turner, Peter J.; Yang, Yongping (Elsevier, 2020)
The solar tower and parabolic trough aided coal-fired power generation has been demonstrated as a promising technology and has potential advantages in utilisation of solar energy in a cost-effective manner. Due to introduction of solar energy, from the solar tower or parabolic troughs, increases to a certain extent, the steam temperature would be difficult to maintain and leads to safety concerns. Therefore, the limitation of integrated solar energy, considering the overlapped influence of different solar energy input, needs to be well identified and managed. This work considered a 600 MWe integrated system as an example. Solar energy from parabolic troughs is used in the preheater while energy from the solar tower is used to reheat steam. The novelty of this study is the interaction of different solar energy input in fossil plants and its benefits is revealed for the first time. The maximum absorbed solar energy, considering the mutual effects of introduced solar energy flows, are explored. Then the system performance under three different loads (100%, 75%, 50%) and hourly operational performance in four typical days are analysed. The paper shows that the feed-water extraction results in the enhancement of maximum solar energy absorbed by reheat steam extraction, is improved by 24.2 MWth (28.5%), 11.5 MWth (20.0%), and 5.6 MWth (14.3%) as feed-water extraction percentages increase at the three load conditions. As a result, the minimum standard coal consumption rates are improved by 13.2 g/kWh (5.2%), 10.7 (4.1%) g/kWh and 9.0 g/kWh (3.1%) respectively. In four typical days, the highest coal consumption reduction is reached in the summer solstice, which is 266.6-tonne, 202.8-tonne and 131.4-tonne under three different loads, while the highest coal consumption is obtained in the winter solstice.
Keywords: Solar tower; Parabolic trough; Coal-fired power generation; Off-design performances